Pembuatan Komik Layanan Perpustakaan Kabupaten Tanah Datar - Muhira, Rahmatina; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
Abstract The purpose of writing this paper is to describe the making of comic library services in the Tanah Datar District Library and Library Office. Writing this paper using descriptive research methods. Data was collected based on interviews with 2 librarians by interacting directly with humans at the place of study. The study was conducted at the Tanah Datar District Public Library on October 21, 2019.Based on the previous discussion it can be concluded that the comic service at the Tanah Datar District Library and Archives Service can provide several benefits including: (1) can provide information to visitors about library services; (2) the librarian's assistant in giving and providing information in the library. The steps for making comic services in the Tanah Datar District Library and Archives Service are as follows: (1) preparing tools and materials; (2) determine ideas or ideas; (3) determine the theme or genre; (4) determining figures or figures; (5) making a story script; (6) explains the stages of making comics.Keywords: comics, services, library